Sztuka radości i praktyka anarchii. O powieści Goliardy Sapienzy i kilku polskich utworach - Lisowska, Katarzyna (Poznańskie Studia Polonistyczne. Seria Literacka, 2020)
The article discusses the Polish translation (2018) of Goliarda Sapienza’s novel L’arte della gioia (The Art of Joy, in Polish Sztuka radości, trans. by Tomasz Kwiecień) in relation to the selected works of Inga Iwasiów and Sylwia Zientek. Anarchism, which provides the ideological background of the Italian book, serves as the basic point of reference for this interpretation. The author points to the issues from Sapienza’s novel which are important from the perspective of anarchism and which can also be found in the Polish texts mentioned in the article. The aim of this analysis is to discuss the context in which The Art of Joy functions in Poland and to suggest the possible lines of interpretation that can be drawn between this novel and contemporary Polish literature.